Timely Reading: Implications of Distributed Cognition for Reading - Trasmundi, Sarah Bro; Mangen, Anne; Kokkola, Lydia (Language and Literacy / Langue et littératie, 2025)
This is a theoretical paper which presents a Distributed Cognition (DCog) perspective on reading that supplements existing approaches to account for phenomena that appear contradictory. The DCog approach moves understandings of reading beyond the individualistic, mental processing of text to a consideration of reading as situated, embodied material engagement that draws on multiple timescales. Drawing on the field of cognitive anthropology, the DCog framework situates reading within an ecology of three closely connected dimensions: 1) mind-body-material environment coordination, 2) distribution across a social group, and 3) distribution across time. By integrating cognitive, affective, sensory-motor, and cultural dimensions, this framework provides a robust approach to understanding contemporary reading practices in complex multimedia environments. The resulting conceptualisation of reading accounts for seeming disparities in existing empirical research without the need for ad hoc adjustments as new reading ecologies emerge, for instance with digitisation. It is also sufficiently simple to promote communication of research findings to practitioners in the field.